Socio Economic Characteristics and Patterns of Decision Making Women’s Fishermen in the City Bengkulu - Romdhon, M. Mustopa; Sukiyono, Ketut (Sodality: Jurnal Sosiologi Pedesaan, 2017)
ABSTRACTThe role of women in the household is a very complex fishermen from productive activity, domestic, and social. Decisions taken fisherman’s wife to engage in such activities is largely determined by socio - economic characteristics of households of fishermen. These characteristics will determine the pattern of decisions taken. How big is women involvement in fishermen decision making.The analytical method used was descriptive analyses. This study indicated social characteristics are age, ethnics, education, number of family members. Economic characteristics, including the distance to the workplace, length of stay, the allocation of working time and the wife revenue contribution to total household income of fishermen. Those characteristics have to consider among household decision making. Currently, their role in the decision making were equal.Current decision-making patterns have an incentive to reduce the dominance of the head of household to monopolize decisions in the household.Keywords: decision making pattern, woman, social – economic characteristicsABSTRAKKeterlibatan wanita pada kegiatan produktif didorong oleh keinginan mereka untuk mencukupi kebutuhan keluarga. Keputusan wanita nelayan terlibat pada aktifitas produktif, domestik dan sosial sangat ditentukan oleh karakteristik sosial ekonomi wanita nelayan. Apa saja karakteristik wanita nelayan dan seberapa besar perannya dalam pengambilan keputusan rumah tangga di Kota Bengkulu. Peran wanita nelayan pada ketiga aktifitas dianalisis dengan metode analisis deskriptif. Hasil penelitian mengindikasikan karakteristik sosial antara lain umur, etnis, pendidikan,jumlah anggota keluarga. Karakteristik ekonomi antara lain lama usaha, jarak ke tempat kerja, lama bermukim, alokasi waktu serta kontribusi pendapatan wanita terhadap pendapatan rumah tangga. Secara umum, peran isteri setara dengan peran suami pada pengambilan keputusan rumah tangga nelayan di Kota Bengkulu.Model pengambilan keputusan akan mendorong untuk mengurangi dominasi suami atau pihak tertentu untuk memonopoli keputusan dalam rumah tangga.Kata kunci: model pengambilan keputusan, wanita, karakteristik sosial-ekonomi